INFLAMASI BOWEL DISEASE - Lipinwati, Lipinwati (Scientific Of Environmental Health and Diseases, 2022)
ABSTRACT Inflammatory Bowel Disease (IBD) is one of public health problems because it will affect patient education, work ability and related with quality of life. IBD is a chronic recurrent inflammation of the small intestine and colon with unknown etiology, with symptoms mild to severe abdominal pain and diarrhea. IBD is divided into 2 types: one is Crohn's disease (CD) which often occurs in the ileum (can extend to the entire gastrointestinal tract) with symptoms of abdominal pain, diarrhea, vomiting and weight loss, and two is Ulcerative colitis (UC) which is characterized by progressive inflammation. in the gastrointestinal tract and colonic mucosa. The etiology of IBD is suspected result of a complex interaction between genetics, role of the gut microbiota, immune system, and specific environmental factors. The pathogenesis of IBD is not clearly known, there is a thought that IBD is caused by a complex role between the gut microbiota, dysregulation of the immune system, role of genetics and environmental factors. Diagnosis is based on history taking, physical examination, supporting examinations such as blood tests, stool cultures, radiological examinations, endoscopic examinations and histopathology. The principle of IBD therapy is treating active IBD inflammation quickly until remission, prevent recurrent inflammation by maintaining remission as long as possible, and treat/prevent complications. The management includes pharmacotherapy, nutrition, surgery and psychotherapy. Keyword: Inflammatory Bowel Disease (IBD), Ulcerative colitis (UC) ABSTRAK Inflamatory Bowel Disease (IBD) merupakan masalah kesehatan masyarakat yang penting karena akan mempengaruhi pendidikan pasien, kemampuan bekerja dan berhubungan dengan kualitas hidupnya. IBD adalah peradangan kronik berulang pada usus halus dan kolon yang belum diketahui penyebabnya dengan gejala sakit perut yang berat dan diare. IBD terbagi atas 2 jenis, yaitu: Crohn’s disease (CD) yang sering terjadi ileum (dapat meluas ke seluruh dinidng saluran cerna) dengan gejala sakit perut, diare, muntah dan penurunan berat badan, dan Ulcerative colitis (UC) yang ditandai dengan peradangan progresif pada sistem saluran cerna dan mukosa kolon. Etiologi IBD secara pasti belum diketahui, diduga IBD merupakan hasil dari interaksi kompleks antara genetik, peran mikrobiota usus, sistem imunitas, faktor lingkungan yang spesifik. Patogenesis IBD secara jelas belum diketahui, adanya pemikiran bahwa IBD disebabkan oleh peran kompleks antara mikrobiota usus, disregulasi sistem imun, peran genetik dan faktor lingkungan. Penegakkan diagnosis berdasarkan anamnesis, pemeriksaan fisik, pemeriksaan penunjang seperti pemeriksaan darah, kultur tinja, pemeriksaan radiologi, pemeriksaan endoskopi dan histopatologi. Prinsip terapi IBD adalah mengobati peradangan aktif IBD dengan cepat sehingga tercapai remisi, mencegah peradangan berulang dengan mempertahankan remisi selama mungkin, dan mengobati/mencegah komplikasi. Manajemen IBD meliputi farmakoterapi, nutrisi, operasi dan psikoterapi. Keyword: Inflamatory Bowel Disease (IBD), Ulcerative colitis (UC)